Family support in adherence to treatment in patients with substance use disorder at the National Institute of Mental Health Hideyo Noguchi in 2021 - García Sobrevilla, Ana Sofía (2023)
Objective: to determine the relationship between family functionality and treatment adherence and compliance in patients with substance abuse disorder in “Instituto Nacional de Salud Mental Hideyo Noguchi – Honorio Delgado” in year 2021. Material and method: quantitative, observational, prospective, descriptive, and cross-sectional study. Our sample was of 153 patients, this was obtained by Epidat program, considering that 80% of patients improves their adherence to treatment with family support, with a precision of 5% and confidence level of 95 %. Three tests were used: APGAR familiar test to size family support, Test de Batalla to size knowledge and Test de Hermes to size treatment adherence. The information was analyzed in SPSS program version 21, using descriptive statistics and chi squared for the relationship of the desired variables. Results: 153 patients were interviewed, 67, 3% of the participants were male and 32,7% female. The average age was 34,62 ± 14,61. 54,20% (n=83) of the patients were unemployed.  The most consumed substance in both sex was alcohol, then marijuana. 71,2% (n=109) had family disfunction in different grades, 17 had severe disfunction. 56,20% (n=86) didn’t have illness knowledge. 75,20% (n=115) had treatment adherence. There was a significant relationship between family support and adherence to treatment of the substance user patient (p = 0,005), but there wasn´t a significant relationship between family accompaniment and illness knowledge (p = 0,204). Conclusions: The majority of patients attended in addictions area of INSM HN-HD had family disfunction in different grades. There was a significant relationship between family support and treatment adherence.